2017
DOI: 10.1080/14767058.2017.1303667
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diagnostic accuracy of Doppler ultrasound of placenta accreta in Egypt

Abstract: The use of ultrasound together with the color Doppler allowed for better prediction of placental invasion of the myometrium prior to obstetrical intervention to improve the maternal and the fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…In correlation analysis, the poor perinatal prognosis was demonstrated to be correlated with fetal hemodynamic parameters of UtA, UA, and MCA and Qdv/Quv. These indexes could be auxiliary indexes for the evaluation of patients' condition and the prediction of perinatal prognosis, consistent with what was found by Maged et al [33].…”
Section: Correlation Between Fetal Hemodynamic Parameterssupporting
confidence: 90%
“…In correlation analysis, the poor perinatal prognosis was demonstrated to be correlated with fetal hemodynamic parameters of UtA, UA, and MCA and Qdv/Quv. These indexes could be auxiliary indexes for the evaluation of patients' condition and the prediction of perinatal prognosis, consistent with what was found by Maged et al [33].…”
Section: Correlation Between Fetal Hemodynamic Parameterssupporting
confidence: 90%
“…Utero-vascular hypervascularity was another factor that presented as significant in our model. In a recent study by Maged et al [22] a total of 100 individuals with a history of Cesarean section were evaluated and compared in two groups, those with accreta and those without accreta. Similar to our study, they found all sonography indices in their study (loss of clear zone, lacunae, utero-vesical hypervascularity, and subplacental hypervascularity) to be significantly higher in the accreta group.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound together with the color Doppler allowed for better prediction of placental invasion of the myometrium prior to obstetrical intervention to improve the maternal and the fetal outcome. The abnormal Doppler findings are loss of retro placental clear zone, intra placental hypervascularity in uterine bladder interface, and blood vessels invading myometrium (10) . MRI accurately predicted placenta accreta with 88% sensitivity and 100% specificity (11) .…”
Section: Introductionmentioning
confidence: 99%